2015
DOI: 10.4236/nm.2015.64023
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Sociocultural Health Belief Model Influencing Health Behaviors among Saudi Stroke Survivors

Abstract: Understanding patients' beliefs of stroke, especially that cultural model which influences the medical management, is important. Professionals normally hold medical knowledge only about stroke, rather than the patients' perceptions, which leads to limitations in cultural competency. Little is known about Saudi stroke survivors' beliefs and behaviors related to their strokes. Methods: A qualitative methodology was used to collect in-depth information from stroke survivors. From March 2010 to October 2014, 45 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…20 Unlike the evil eye which emanates from humans, spirit possession and black magic emanate from supernatural power; therefore, it is less common. [21][22][23] Surprisingly, despite that these causation beliefs about epilepsy could be in line with some Islamic literatures which linked epilepsy with supernatural power (vide infra), there are no direct prophet's saying (Hadith) that ascribes seizures to Jinni or to evil powers. In his most famous book, "The Canon of Medicine," 24 Avicenna (Ibn Sina) defined the term of "epilepsy" as being possessed by an outside supernatural power.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…20 Unlike the evil eye which emanates from humans, spirit possession and black magic emanate from supernatural power; therefore, it is less common. [21][22][23] Surprisingly, despite that these causation beliefs about epilepsy could be in line with some Islamic literatures which linked epilepsy with supernatural power (vide infra), there are no direct prophet's saying (Hadith) that ascribes seizures to Jinni or to evil powers. In his most famous book, "The Canon of Medicine," 24 Avicenna (Ibn Sina) defined the term of "epilepsy" as being possessed by an outside supernatural power.…”
Section: Discussionmentioning
confidence: 81%
“…Muslims believe that reading the Quran is more essential in case of having problems that could be caused by evil eye or supernatural powers. 22,23 Muslims believe that reading the Quran may not only cure the physical symptoms but also improve mood and lower blood pressure. 28,29 Honey, holy water (Zamzam), and onion seeds are the most Islamic herbal medications that have been used to cure several illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual practices were among the most common complementary interventions that patients held and practised, reflecting the importance of spirituality in Saudi society [34]. A Muslim frequently seeks spiritual healing, such as prayers and reading the Quran, for curing all illness [35]. A result of a recent meta-analysis study suggests greater spirituality is associated with better health improvement among cancer patients [36].…”
Section: Complementarymentioning
confidence: 99%
“…16 People in Western countries practice herbal medicine, reflexology, aromatherapy, massage, osteopathy, meditation, and spiritual healing; 10,[17][18][19] by contrast, those in Asian countries such as China, India, and Taiwan commonly use therapies such as traditional Chinese medicine, Ayurvedic medicine, physical exercises, acupuncture, Tai Chi, yoga, and homeopathy. [20][21][22][23] In Saudi Arabia, different types of CAM are used including the Quran recitation therapy, honey consumption, plantbased traditional medicine (e.g., Murrah and black seed consumption), cupping ("Hojamah"), and cauterization ("skin ironing") 9, [24][25][26][27] Research highlighted that aside from their potential benefits, some types of CAM have many side effects and potential toxicities, and patients are commonly unaware of these possible dangers. 28 One study reported 2 cases wherein the cauterization led to severe complications, such as skin burn.…”
mentioning
confidence: 99%